The mental health of Swiss elite athletes - Röthlin, P.; Horvath, S.; Ackeret, N.; Peter, C.; Birrer, D. (Swiss Psychology Open, 2023)
Mental health is an important topic in competitive sports, but there is only limited data from Switzerland. Although mental health is a prominent topic, it is difficult to estimate the efforts of Swiss sports federations to promote mental health. A representative sample of Swiss athletes (N = 1003, Mage = 21.69, SDage = 7.09, 54% women, 37% team sports, 10% injured) answered questions about symptoms of mental health problems and their well-being. We also asked about the extent of basic need satisfaction and perceived organizational support. Overall, the numbers on symptoms of mental health problems (17% depression, 10% anxiety, 22% eating disorders, 18% sleep disorders) and well-being are comparable to other elite sport samples and the general Swiss population. However, we found large group differences. For example, 52% of women athletes were affected by at least one mental disorder symptom, compared with 30% of men athletes. Injured athletes were most affected in terms of depressive symptoms. The study also shows that need satisfaction and frustration in conjunction with demographic factors is related to well-being and symptoms of mental health problems. Furthermore, the more support athletes perceive from their federations, the better their mental health. We conclude that a substantial proportion of athletes are affected by symptoms of mental disorders and more measures are needed to improve this situation, for example through supporting need satisfaction in the sport setting.